Acquisition of Predictable Vertical Visual Targets: Eye-Head Coordination and the Triggering Effect. Issue 6 (1st November 2016) - Kolev, Ognyan I.; Reschke, Millard F.
ABSTRACT: The study was designed to investigate target acquisition in the vertical plane with emphasis on establishing strategy differences associated with acquisition triggering methods. Eight subjects were tested. Measurements consisted of target acquisition time, eye-head latency differences, velocity of gaze, eyes and head, and head amplitude. Using 3-way repeated measures analyses of variance the results show that the strategy for acquisition of predictable visual targets in vertical plane with the head unrestrained significantly depended on (a) the direction of the gaze motion with respect to the gravity vector (i.e., there is significant up-down asymmetry), (b) the angular distance of the target, and (c) the method of triggering the command to acquire the target—external versus internal. The data also show that when vertical acquisition is compared with triggering methods in the horizontal plane there is a difference in overall strategy for the acquisition of targets with the same spatial distances from straight ahead gaze when both the eyes and head are used. Among the factors contributing to the difference in strategy for vertical target acquisition are the gravitational vector, the relationship of target displacement and vestibular activitation, biomechanical and neural control asymmetries, and the difference in the vertical field of view.